Perceptions of physical education teachers and coaches toward talent identification in volleyball and artistic gymnastics - William Andri Utomo; Nuridin Widya Pranoto; Syahrial Bahktiar; Muhamad Sazeli Rifki (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This study aimed to analyze the perceptions of Physical Education teachers and coaches regarding talent identification in volleyball and artistic gymnastics. A descriptive quantitative design was employed involving 45 respondents, comprising 15 Physical Education teachers, 15 volleyball coaches, and 15 artistic gymnastics coaches selected through total sampling in Tugumulyo District, Musi Rawas Regency, Indonesia. Data were collected using validated and reliable four-point Likert-scale questionnaires and analyzed descriptively using percentage statistics. The findings revealed that overall perceptions were predominantly categorized as good (43%), followed by sufficient (37%), while coaches consistently demonstrated higher perception scores than Physical Education teachers across environmental, anthropometric, physical ability, and psychological indicators. These findings indicate that professional roles and practical experience influence perceptions of talent identification, highlighting the need for stronger collaboration between schools and sports clubs to improve evidence-based talent identification systems.